Iatrogenic Bowel Traversal during Percutaneous Drainage Catheter Placement: A Single-Center Retrospective Review of 3,507 Procedures - Nakanote, Ken; Kaufman, Claire; Weintraub, Michael; Quencer, Keith (Digestive Disease Interventions, 2022)
Image-guided drainage catheter placement is a commonly performed procedure. While the complication rate is low, one potential complication is iatrogenic bowel traversal (IBT). Prior literature reported up to a 3.0% incidence of IBT events. This retrospective review examined image-guided percutaneous abscess catheter placements over 82 months to characterize the incidence, risk factors, and outcomes of IBT. Of 3,507 catheters placed, there were 13 IBT events, conferring a 0.4% incidence. Rates of IBT were similar whether ultrasound and fluoroscopy or computed tomography was utilized for placement. Of these 13 IBT events, 2 were transgastric, 1 was transcolonic, and 10 were through small bowel. Of these events, one patient died of vasopressor refractory septic shock, four underwent operative repair of the enterotomy, and eight were managed with catheter placement and gradual downsizing. The Society of Interventional Radiology Adverse Event Severity Scale was utilized to further categorize IBT events with observed severity ranging from moderate to life threatening. Although overall incidence has decreased since 35 years ago, IBT events are potentially life-threatening adverse events and further study to identify and minimize risk factors is essential.
Keywords: high-risk procedure; intra-abdominal abscess; percutaneous abscess drainage